2020
DOI: 10.1534/g3.119.400838
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Induced and Natural Variation at oil yellow1 Delays Reproductive Maturity in Maize

Abstract: We previously demonstrated that maize (Zea mays) locus very oil yellow1 (vey1) encodes a putative cis-regulatory expression polymorphism at the magnesium chelatase subunit I gene (aka oil yellow1) that strongly modifies the chlorophyll content of the semi-dominant Oy1-N1989 mutants. The vey1 allele of Mo17 inbred line reduces chlorophyll content in the mutants leading to reduced photosynthetic output. Oy1-N1989 mutants in B73 reached reproductive maturity four days later than wild-type siblings. Enhancement of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(43 citation statements)
references
References 92 publications
(164 reference statements)
8
34
1
Order By: Relevance
“…The single locus testing of oy1-vey1 interactions for these traits were tested directly using NIL x tester crosses. We found stalk widths of Oy1-N1989 mutants were narrower than wildtype siblings and this was enhanced by the vey1 Mo17 allele, just as we previously found for chlorophyll content, net CO2 assimilation, and time to reproductive maturity (Khangura et al 2019a(Khangura et al , 2019b. To our surprise, we found that plant height in the Oy1-N1989 mutants can be either greater or less than their congenic wildtype siblings.…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…The single locus testing of oy1-vey1 interactions for these traits were tested directly using NIL x tester crosses. We found stalk widths of Oy1-N1989 mutants were narrower than wildtype siblings and this was enhanced by the vey1 Mo17 allele, just as we previously found for chlorophyll content, net CO2 assimilation, and time to reproductive maturity (Khangura et al 2019a(Khangura et al , 2019b. To our surprise, we found that plant height in the Oy1-N1989 mutants can be either greater or less than their congenic wildtype siblings.…”
Section: Introductionsupporting
confidence: 82%
“…The plant height and stalk width were measured in both wildtype (WT) and mutant (MT) siblings segregating in each family in the F1 populations of Oy1-N1989/+:B73 with the IBM , Syn10, and NIL populations. As described previously (Khangura et al 2019a(Khangura et al , 2019b, genetic backgrounds containing the vey1 B73 allele progressively suppresses the mutant phenotype and were tagged at V5-V7 stage when they were distinguishable from the wildtype siblings so that traits could be recorded at maturity when the genotypes are harder to distinguish. Trait measurements were performed on two to four WT and MT siblings that were picked at random.…”
Section: Phenotyping and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations